A mitochondria-targeted ratiometric fluorescence sensor for the detection of hypochlorite in living cells. (December 2019) - Wang, Wei; Ning, Jun-Ya; Liu, Jin-Ting; Miao, Jun-Ying; Zhao, Bao-Xiang
Abstract: A new fluorescence probe based on phenothiazine-coumarin platform was rationally designed and developed for the detection of hypochlorite in a ratiometric manner in aqueous solution and living cells. The probe possessed a large pseudo Stokes shift (209 nm) and lager gap between two emissions (462/629 nm), which should avail to perform more accurate detection. The probe could respond to hypochlorite with selectivity, sensitivity and celerity. Moreover, the probe was successfully used for imaging endogenous hypochlorite in mitochondria of RAW264.7 macrophage cells with high sensitivity. Graphical abstract: Image 1 Highlights: A novel ratiometric fluorescent probe (named PPC) for hypochlorite based on FRET platform was developed. PPC showed a large pseudo Stokes shift (209 nm), high selectivity, sensitivity and fast response. PPC could target well mitochondria in cell image. PPC could image endogenous hypochlorite in RAW264.7 cells.